The administration of national elections: A comparative analysis and the case of Egypt. - Canaan, Marie Ramona (AUC Knowledge Fountain, 2015)
This study introduces policy directive outlines and important considerations in relation to the design of the National Electoral Authority organigram- the new electoral management body- NEA- stated in the 2014 Egyptian constitution. The suggested structure is based on a range of the most widely used electoral administration options and a comparative study of three different countries. It also recalls relevant principles of international electoral principles policies and practices.